Carbon-cement-based super energy storage material as well as preparation method and application thereof
By introducing nanocarbon black powder and cured capsule composite materials into carbon-cement-based super energy storage materials, an electronic conductive carbon network structure is formed with a high specific surface area, which solves the problems of large interface impedance and low ionic conductivity of existing materials, and achieves the effect of efficient energy storage and long life.
Patent Information
- Application Number
- CN202411693785.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-14
AI Technical Summary
The existing carbon-cement-based super energy storage materials have problems such as large interface impedance, low ionic conductivity, short service life and low capacity, which limits their applications in sustainable residential and industrial fields.
By mixing cement with nanocarbon black powder, adding water reducing agent and curing capsule composite material, an electronically conductive carbon network structure is formed with a high specific surface area, which promotes the cement-based material to form a porous energy storage template during the hydration process, and achieves efficient storage and transmission of charge.
It has achieved high specific surface area, high mechanical properties, high energy storage capacity and high efficiency charging and discharging capabilities, significantly improving the conductive and energy storage characteristics of the material, extending the service life, and enhancing the adaptability with concrete structural materials.
Smart Images

Figure CN119613040A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy storage materials, and in particular to a carbon-cement-based super energy storage material and a preparation method and application thereof. Background Art
[0002] Scalable carbon-cement-based super energy storage materials have excellent conductive and energy storage properties such as high specific surface area, high mechanical properties, high energy storage capacity, and high-efficiency charge and discharge capabilities. The high specific surface area electronic conductive carbon network structure formed by the depolymerization and recombination of carbon black particles can prompt cement-based materials to generate porous energy storage templates with micron / submicron-scale saturated electrolyte reservoirs during the hydration process, thereby achieving scalability for efficient storage and transmission of charges from the electrode scale to the structural scale. It has broad application prospects in sustainable residential and industrial applications such as isolated buildings or shelters far away from the power grid, electric vehicle self-charging roads, and intermittent energy storage in wind turbines and tidal power stations.
[0003] At present, there are two main methods for synthesizing this type of material: embedded integration and multifunctional materials. Embedded integration directly embeds energy storage devices into the structure, which can easily cause the interface to be weak and make it difficult to exert the mechanical properties of the structure; multifunctional materials are more continuous inside and the interface is tighter, with higher energy and structural efficiency, but there are problems such as low ion conductivity, large interface impedance, and poor interface stability; cement-based functional materials have problems such as small discharge current (mostly μA or mA level), short service life (mostly in hours and days) and low capacity (mostly mAh level), so their application is greatly limited. Therefore, the preparation of a carbon-cement-based super energy storage material with good mechanical properties, low manufacturing cost and compatibility with concrete structural materials is of great significance for giving structures energy storage functions and developing renewable energy systems. Summary of the invention
[0004] The purpose of the present invention is to provide a carbon-cement-based super energy storage material and a preparation method and application thereof in view of the above-mentioned deficiencies in the prior art.
[0005] A method for preparing a carbon-cement-based super energy storage material of the present invention comprises the following steps:
[0006] S1, mixing cement and nano carbon black powder to obtain a solid nano composite material a;
[0007] S2, adding the water reducing agent and the curing capsule composite material into deionized water, stirring until dissolved, to obtain a solution b;
[0008] S3, mixing the solid nanocomposite material a, the solution b and deionized water to obtain a mixed slurry c;
[0009] S4, pouring, curing and demoulding the mixed slurry c to obtain a carbon-cement-based composite material d;
[0010] S5, cutting the carbon-cement-based composite material d into thin slices, polishing the slices, and then completely immersing the slices in an electrolyte solution to obtain a carbon-cement-based super energy storage material;
[0011] Among them, the cured capsule composite material is the PNCH-Pt / TiO2-g-C3N4 nanocomposite material disclosed in Chinese Patent 2024102080945.
[0012] Furthermore, the mass ratio of cement to nano carbon black powder is 0.1-0.23.
[0013] Furthermore, the water reducer is a polynaphthalenesulfonate high-efficiency water reducer; the mass ratio of the water reducer to the cured capsule composite material is 1:1, and in solution b, the mass ratio of the water reducer to deionized water is 0.6-1.1:5.
[0014] Furthermore, the liquid-to-solid ratio in the mixed slurry c is 0.4-0.8.
[0015] Furthermore, the specific operation of step S4 is: pouring the mixed slurry c into a polycarbonate mold, sealing both ends with plastic wrap, immersing it in a lime solution, transferring it to a curing box for standard curing for 28 days, and then demolding it.
[0016] Furthermore, the thickness of the sheet is 0.18-1.00 cm.
[0017] Furthermore, the electrolyte solution is a standard potassium chloride solution; and the soaking time is 1-2 hours.
[0018] Furthermore, the nano carbon black powder is one of PBX 55, Vulcan XC72 and Ketjenblack EC-600JD; and the cement is Portland cement powder.
[0019] A carbon-cement-based super energy storage material prepared by the above-mentioned preparation method.
[0020] The carbon-cement-based super energy storage material as described above is used to prepare a supercapacitor.
[0021] The present invention adds a solidified capsule composite material, which belongs to a nanocomposite polymer and has a three-dimensional cross-linked molecular network. The network can generate three-dimensional layered hydration products through covalent or non-covalent interactions (including physical entanglement, hydrogen bonding, hydrophobic interaction, supramolecular interaction, electrostatic interaction and ligand interaction, etc.). The solidified capsule composite material has a strong targeted chemical binding ability for heavy metals and chloride ions, so that the heavy metals and chloride ions in cement can be adsorbed on the surface of its three-dimensional grid structure, making the interior of the energy storage material more continuous and the interface more compact.
[0022] The carbon-cement-based super energy storage material prepared by the present invention has excellent electrical conductivity and energy storage properties such as high specific surface area, high mechanical properties, high energy storage capacity, and high-efficiency charge and discharge capabilities. At the same time, through the high specific surface area electronic conductive carbon network structure, the cement-based material can be prompted to generate a porous energy storage template with a micron / submicron saturated electrolyte reservoir during the hydration process, thereby achieving scalability for high-efficiency storage and transmission of charges from the electrode scale to the structural scale, providing a necessary solution for large-scale energy storage systems, and can be widely used in sustainable residential and industrial fields such as isolated buildings or shelters far away from the power grid, electric vehicle self-charging roads, and intermittent energy storage of wind turbines and tidal power stations.
[0023] In summary, scalable carbon-cement-based super energy storage materials can significantly improve the Seebeck coefficient of concrete materials without changing the performance of concrete materials due to their structural adaptability with concrete materials, making self-generation and self-storage of concrete possible, thereby promoting the use of renewable energy such as solar energy, wind energy and tidal energy. This breakthrough is expected to have a significant market impact in a short period of time.
[0024] The scalable carbon-cement-based super energy storage material prepared by the present invention belongs to a quasi-solid electrolyte and has excellent electrical conductivity and energy storage properties such as high specific surface area, high mechanical properties, high energy storage capacity, and high-efficiency charge and discharge capabilities. The ionic conductivity at room temperature exceeds 2.0×10 -2 S cm -1 , the maximum energy density is 8.0Wh / m 2 .
[0025] The scalable carbon-cement-based super energy storage material prepared by the present invention has the scalability of high-efficiency storage and transmission of charge from electrode scale to structural scale, that is, a 1 mm thick electrode can be expanded to a 1 m thick electrode or a 45 m thick electrode. 3 Small-scale carbon-cement-based super energy storage materials doped concrete can store about 10kW·h of electrical energy, providing a solution for large-scale energy storage systems.
[0026] The scalable carbon-cement-based super energy storage material prepared by the present invention has broader application scenarios, such as green energy storage buildings, concrete smart structures and energy-collecting concrete. Through reasonable battery design, it can be widely used in sustainable residential and industrial fields such as isolated buildings or shelters far away from the power grid, electric vehicle self-charging roads, intermittent energy storage of wind turbines and tidal power stations. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The present invention is a flow chart for preparing the carbon-cement-based super energy storage material;
[0028] Figure 2 This is a SEM image of the P-type carbon-cement-based super energy storage material prepared in Example 1;
[0029] Figure 3 This is a SEM image of the carbon-cement-based super energy storage material prepared using different types of carbon black as raw materials in Example 3;
[0030] Figure 4 Cyclic voltammetry (CV) curves of the carbon-cement-based super energy storage materials prepared in Examples 1 and 2 at different scan rates;
[0031] Figure 5 Chronopotentiometry (GCD) curves of the carbon-cement-based super energy storage materials prepared in Examples 1 and 2 at different current densities;
[0032] Figure 6 is the cycle performance diagram of KE2 within 5000 cycles;
[0033] Figure 7 These are the mechanical test results of the carbon-cement-based super energy storage materials prepared in Examples 1-3. DETAILED DESCRIPTION
[0034] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.
[0035] Example 1
[0036] Portland cement powder (C) and nano carbon black powder of model PBX 55 (Cabot conductive carbon black) were used to prepare P-type carbon-cement-based super energy storage materials at different liquid-to-solid ratios (W / C). Figure 1 As shown, the specific steps are as follows:
[0037] 1) In an air environment, Portland cement powder (C) and nano carbon black powder (CB) of model PBX 55 are mixed according to the mass ratio given in Table 1 (specific masses are shown in Table 1), and stirred continuously for 5-10 minutes to obtain a solid nano composite material a;
[0038] 2) In an air environment, polynaphthalenesulfonate high-efficiency water reducer (PNS-HRWRA) and cured capsule composite material (CCs) were added to 5 mL of deionized water at a mass ratio of 1:1 (specific masses are shown in Table 1), and stirred until dissolved to obtain solution b;
[0039] 3) In an air environment, the solid nanocomposite material a and the solution b are mixed, and a certain volume of deionized water is added, and the mixture is continuously stirred for 5-10 minutes to obtain a mixed slurry c having a liquid-to-solid ratio (W / C) given in Table 1;
[0040] 4) In an air environment, the mixed slurry c was poured into a polycarbonate mold with a diameter of 2.2 cm, the two ends were sealed with plastic wrap, immersed in a lime solution, transferred to a curing box and cured for 28 days before demoulding to obtain a carbon-cement-based composite material d;
[0041] 5) In an air environment, the carbon-cement-based composite material d was cut into thin slices with a thickness of 0.25 cm using a slow diamond saw. After its surface was polished with silicon carbide paper, it was completely immersed in a standard potassium chloride (KCl) electrolyte solution to obtain three P-type carbon-cement-based super energy storage materials P1, P2, and P3.
[0042] Table 1. Material ratio of P-type carbon-cement-based super energy storage materials
[0043]
[0044] Note: W / C is liquid-to-solid ratio; n CB / C is the mass ratio of nano carbon black powder (CB) to Portland cement powder (C); d is the electrode thickness.
[0045] Example 2
[0046] Portland cement powder (C) and nano carbon black powder of model PBX 55 (Cabot conductive carbon black) are used to prepare PE-type carbon-cement-based super energy storage materials with electrodes of different thicknesses at a liquid-to-solid ratio (W / C) of 0.8, comprising the following steps:
[0047] 1) In air environment, Portland cement powder (C) and nano carbon black powder (CB) of model PBX 55 were mixed in the mass ratio (n CB / C =0.224) and stirred continuously for 5-10 minutes to obtain a solid nanocomposite material a;
[0048] 2) In an air environment, polynaphthalenesulfonate high-efficiency water reducer (PNS-HRWRA) and cured capsule composite material (CCs) were added to 5 mL of deionized water at a mass ratio of 1:1 (specific masses are shown in Table 2), and stirred until dissolved to obtain solution b;
[0049] 3) In an air environment, the solid nanocomposite material a and the solution b are mixed, and deionized water is added, and the mixture is stirred continuously for 5-10 minutes to obtain a mixed slurry c having a liquid-to-solid ratio (W / C=0.8) given in Table 2;
[0050] 4) In an air environment, the mixed slurry c was poured into a polycarbonate mold with a diameter of 2.2 cm, the two ends were sealed with plastic wrap, immersed in a lime solution, transferred to a curing box and cured for 28 days before demoulding to obtain a carbon-cement-based composite material d;
[0051] 5) In an air environment, the carbon-cement-based composite material d was cut into thin sheets with a thickness of 0.18-1.00 cm using a slow diamond saw, and its surface was polished with silicon carbide paper. It was then completely immersed in a standard potassium chloride (KCl) electrolyte solution to obtain three PE-type carbon-cement-based super energy storage materials PE1, PE2, and PE3.
[0052] Table 2. Material ratio of P-type carbon-cement-based super energy storage materials
[0053]
[0054] Note: W / C is liquid-to-solid ratio; n CB / C is the mass ratio of nano carbon black powder (CB) to Portland cement powder (C); d is the electrode thickness.
[0055] Example 3
[0056] Three types of nano carbon black powder [PBX 55 (Cabot conductive carbon black), Vulcan XC72 (Cabot special antistatic conductive carbon black), Ketjenblack EC-600JD (Nouryon super conductive carbon black)] were respectively mixed with Portland cement powder (C) at a liquid-to-solid ratio (W / C) of 0.8 to prepare carbon-cement-based super energy storage materials with electrodes of different thicknesses, including the following steps:
[0057] 1) In an air environment, three types of nano carbon black powder (CB) (PBX 55, Vulcan XC72, Ketjenblack EC-600JD) were mixed with Portland cement powder (C) according to the mass ratio given in Table 3, and stirred continuously for 5-10 minutes to obtain three solid nanocomposites CPB, CVB, and CKB;
[0058] 2) In an air environment, polynaphthalenesulfonate high-efficiency water reducer (PNS-HRWRA) and cured capsule composite material (CCs) were added to 5 mL of deionized water at a mass ratio of 1:1 (specific masses are shown in Table 3), and stirred until dissolved to obtain solution b;
[0059] 3) In an air environment, three solid nanocomposites CPB, CVB, CKB and solution b were mixed, deionized water was added, and the mixture was stirred continuously for 5-10 minutes to obtain a mixed slurry c having a liquid-to-solid ratio (W / C=0.8) given in Table 3;
[0060] 4) In an air environment, the mixed slurry c was poured into a polycarbonate mold with a diameter of 2.2 cm, the two ends were sealed with plastic wrap, immersed in a lime solution, transferred to a curing box and cured for 28 days before demoulding to obtain a carbon-cement-based composite material d;
[0061] 5) In an air environment, the carbon-cement-based composite material d was cut into thin slices with a thickness of 0.26-0.34 cm using a slow diamond saw. After its surface was polished with silicon carbide paper, it was completely immersed in a standard potassium chloride (KCl) electrolyte solution to obtain three carbon-cement-based super energy storage materials PE2, VE2, and KE2.
[0062] Table 3. Material ratio of carbon-cement-based super energy storage materials
[0063]
[0064] Note: W / C is liquid-to-solid ratio; n CB / C is the mass ratio of nano carbon black powder (CB) to Portland cement powder (C); d is the electrode thickness.
[0065] Figure 1 It is a preparation flow chart of the carbon-cement-based super energy storage material of the present invention; the first step is to generate a mixed cement slurry by carbon black and cement, the second step is to add additives such as a water reducer and a curing capsule composite material to prepare a phosphorus-cement-based composite material after curing for 28 days, the third step is to form a porous energy storage template after cutting into thin slices and soaking in a standard electrolyte solution, and the fourth step is to detect the energy storage material for charge transfer and storage, and determine the anode and cathode.
[0066] Figure 2 This is the SEM image of the P-type carbon-cement-based super energy storage material prepared in Example 1. Figure 2 It can be seen that different solids and liquids have a significant impact on the microstructure of the prepared P-type carbon-cement-based super energy storage material: a higher water-cement ratio helps to improve the ion transmission speed and ion migration, but it will sacrifice the density and mechanical strength of the material. On the contrary, a lower water-cement ratio optimizes the mechanical strength and density, and improves the cycle stability and energy density of the energy storage material, but smaller pores and high density may limit the migration speed of ions and affect the ion transmission capacity of the material.
[0067] Figure 3 The SEM images of the carbon-cement-based super energy storage materials prepared using different types of carbon black as raw materials in Example 3 are shown in FIG. Figure 3 It can be seen that the microstructure is very different, which also has a corresponding impact on the subsequent material charge transfer and storage. The specific explanation is as follows:
[0068] The SEM image of PE2 shows a relatively dense surface with a certain continuity between particles. The microstructure is blocky and rough, indicating that PBX 55 carbon black may have a larger particle diameter and a lower specific surface area. The SEM image of VE2 shows a relatively uniform and fine particle structure, and the interface between the particles is relatively fuzzy. This structure is usually conducive to the improvement of electrochemical performance while maintaining good overall uniformity of the material. The SEM image of KE2 shows obvious flaky and layered structure. The obvious pores and irregular morphology indicate that this material may have a higher porosity, which is conducive to the rapid transmission of ions and electrons, but too high a porosity may have a certain impact on the stability of the material.
[0069] Figure 4 Cyclic voltammetry (CV) curves of carbon-cement-based super energy storage materials prepared in Examples 1 and 2 at different scan rates; (a) 10 mV·s -1 (b) 30 mV·s -1 ; (c) 100mV·s -1 .
[0070] Depend on Figure 4 (a) It can be seen that the CV curve is close to a rectangle, indicating that the material has good electrochemical double-layer capacitance behavior; the P series (especially P1 and P2) shows a curve shape closer to the ideal double-layer capacitance, indicating that it has excellent energy storage performance and low impedance characteristics; the PE3 curve of the PE series is slightly distorted, indicating that its electrochemical performance is subject to certain limitations, which may be caused by larger charge transfer impedance or lower conductivity.
[0071] Depend on Figure 4 (b) It can be seen that when the scan rate increases, the current density of all samples increases, indicating that the material has a strong ability to react quickly to electrochemical reactions; the curves of P1 and P2 are still close to rectangles, indicating that they maintain good electrochemical behavior at medium scan rates; the curve distortion of PE3 is more obvious, which may indicate that its ion diffusion is significantly restricted at medium scan rates; the curve areas of P3 and PE1 are larger, indicating that they have a higher charge storage capacity at this scan rate.
[0072] Depend on Figure 4(c) It can be seen that when the scan rate is further increased, the curves of all samples are distorted, mainly due to the current hysteresis caused by the kinetic limitation of ion diffusion; the curves of the P series samples (especially P1 and P2) are still relatively symmetrical, indicating that they have higher charge / ion transfer rates and lower internal impedance; the severe distortion of the PE3 curve indicates that its electrochemical performance is significantly limited at high scan rates, which may be caused by insufficient pore design of the material or unstable electrode structure.
[0073] In summary, in terms of electrochemical performance, the P series is better than the PE series as a whole, as shown by a larger CV area and good curve symmetry, reflecting a higher charge storage capacity and a faster charge transfer rate; in terms of rate, as the scan rate increases, the CV curves of all materials show a certain degree of distortion, but the P series has significantly better rate resistance, especially P1.
[0074] Figure 5 Chronopotentiometry (GCD) curves of carbon-cement-based super energy storage materials prepared in Examples 1 and 2 at different current densities; (a) 0.5 mA·cm -2 ; (b) 1 mA cm -2 ; (c) 5 mA cm -2 .
[0075] Depend on Figure 5 (a) It can be seen that at low current density, the discharge time of all samples is relatively long, indicating that at a relatively small current, the electrode material can exhibit a relatively high capacity performance (excellent electrochemical energy storage performance); the discharge time of the PE series samples is shorter than that of the P series, indicating that the specific capacitance of the PE series materials is slightly lower or the material conductivity is relatively poor.
[0076] Depend on Figure 5 (b) It can be seen that after the current density increases, the discharge time of all samples is significantly shortened compared with (a), indicating that the current density has a significant effect on the electrochemical properties of the material; the differences between different samples are more obvious. For example, the discharge time of PE3 is significantly the shortest, indicating that the capacity attenuation of this material is large at high current density, which may be related to its conductivity or ion diffusion limitation.
[0077] Depend on Figure 5 (c) It can be seen that under high current density, the discharge time is further shortened, indicating that the capacity of the material decreases under rapid charge and discharge; the capacity decrease of the PE series is particularly significant (especially PE3), indicating that it may have a large internal resistance or ion diffusion resistance; the P series shows relatively higher stability, especially P1, which may benefit from its excellent conductivity and ion transmission channel.
[0078] In summary, as the current density increases, the discharge time of all materials shortens, indicating that at high current density, the polarization effect and ion diffusion limitation have a greater impact on the electrochemical performance; the P series samples show better performance than the PE series, and different electrode thicknesses have a greater impact on the conductivity and ion diffusion capacity of the generated materials.
[0079] Figure 6 This is the cycle performance diagram of KE2 within 5000 cycles. Figure 6 It can be seen that the capacitance retention rate is close to 93.8%, indicating that the KE2 sample can still maintain a high specific capacitance after 5000 cycles, showing excellent cycle stability; the coulombic efficiency is always maintained at around 99.6%, almost close to 100%, indicating that the storage and release process of charge is highly reversible during each charge and discharge process. At the same time, the high coulombic efficiency reflects the high efficiency of the charge transfer and ion diffusion process in the KE2 sample, and the electrode material has no obvious side reactions or irreversible losses during the cycle; from the comparison of the voltage curves of 1-6 and 3995-4000 cycles, the shape of the charge and discharge curves is basically the same, indicating that the electrochemical reaction mechanism of the material has no obvious changes in long-term cycles, and the voltage platform is stable, which further verifies the good cycle life and structural stability of the KE2 material.
[0080] Figure 7 The mechanical test results of the carbon-cement-based super energy storage materials prepared in Examples 1-3. Figure 7 It can be seen that the carbon-cement-based super energy storage material prepared by 3 has good mechanical properties.
[0081] For matters not mentioned above, the prior art applies.
[0082] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon-cement-based super energy storage material, characterized in that: The steps include: S1, mixing cement and nano carbon black powder to obtain a solid nano composite material a; S2, adding the water reducing agent and the curing capsule composite material into deionized water, stirring until dissolved, to obtain a solution b; S3, mixing the solid nanocomposite material a, the solution b and deionized water to obtain a mixed slurry c; S4, pouring, curing and demoulding the mixed slurry c to obtain a carbon-cement-based composite material d; S5, cutting the carbon-cement-based composite material d into thin slices, polishing the slices, and then completely immersing the slices in an electrolyte solution to obtain a carbon-cement-based super energy storage material; Among them, the cured capsule composite material is the PNCH-Pt / TiO2-g-C3N4 nanocomposite material disclosed in Chinese Patent 2024102080945.
2. The preparation method according to claim 1, characterized in that: The mass ratio of cement to nano carbon black powder is 0.1-0.
23.
3. The preparation method according to claim 1, characterized in that: The water reducer is a polynaphthalenesulfonate high-efficiency water reducer; the mass ratio of the water reducer to the cured capsule composite material is 1:1, and in solution b, the mass ratio of the water reducer to deionized water is 0.6-1.1:
5.
4. The preparation method according to claim 1, characterized in that: The liquid-to-solid ratio in the mixed slurry c is 0.4-0.
8.
5. The preparation method according to claim 1, characterized in that: The specific operation of step S4 is: pouring the mixed slurry c into a polycarbonate mold, sealing both ends with plastic wrap, immersing it in a lime solution, transferring it to a curing box for standard curing for 28 days, and then demolding it.
6. The preparation method according to claim 1, characterized in that: The thickness of the sheet is 0.18-1.00 cm.
7. The preparation method according to claim 1, characterized in that: The electrolyte solution is a standard potassium chloride solution; the soaking time is 1-2 hours.
8. The preparation method according to claim 1, characterized in that: The nano carbon black powder is one of PBX 55, Vulcan XC72 and Ketjenblack EC-600JD; the cement is Portland cement powder.
9. A carbon-cement-based super energy storage material prepared by the preparation method according to any one of claims 1 to 8.
10. The carbon-cement-based super energy storage material as claimed in claim 9 is used for preparing super capacitors.